USM TO FOCUS ON BALANCED EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 October 2016 – Universiti Sains Malaysia (USM) would focus on nurturing balanced graduates who have acquired knowledge and are welldeveloped in character, and able to integrate the Sciences and the Arts in a holistic manner.